1993
DOI: 10.1073/pnas.90.18.8752
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human insulin-like growth factor I exerts a trophic action and confers glutamate sensitivity on glutamate-resistant cerebellar granule cells.

Abstract: Cerebelwar granule cells grown in the presence of a serum complex differentiate but are resistant to the kthal action of excitatory amino acids. When these cells are grown also in the presence of insuln-like growth factor I (IGF-I) they become fuly susceptible to the toxic, lethal action of glutamate. The glutamate-sensitizing action of IGF-I is dependent on concentration (half-maximal effect at 2-4 ng/ml) and time (half-mxidmal effect at 2-4 days in vitro) and is paralleled by the appearance of functionally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…It has been recently reported that the coadministration of IGF-I and glutamate into the cerebellar cortex and the deep cerebellar nuclei greatly depresses the release of GABA, which normally follows a glutamate pulse and that electrical stimulation of the inferior olivary complex significantly raises IGF-I levels in the cerebellar cortex (Castro-Alamancos and Torres-Aleman, 1993). More recent findings suggest that the responsiveness of cerebellar granule cells to glutamate in vivo might be epigenetically regulated by IGF-I (Calissano et al, 1993). Taken together these data indicate a role for IGF-I in modulating the neural activity within certain areas of the mature CNS.…”
Section: Irs-i-immunoreactivesupporting
confidence: 48%
“…It has been recently reported that the coadministration of IGF-I and glutamate into the cerebellar cortex and the deep cerebellar nuclei greatly depresses the release of GABA, which normally follows a glutamate pulse and that electrical stimulation of the inferior olivary complex significantly raises IGF-I levels in the cerebellar cortex (Castro-Alamancos and Torres-Aleman, 1993). More recent findings suggest that the responsiveness of cerebellar granule cells to glutamate in vivo might be epigenetically regulated by IGF-I (Calissano et al, 1993). Taken together these data indicate a role for IGF-I in modulating the neural activity within certain areas of the mature CNS.…”
Section: Irs-i-immunoreactivesupporting
confidence: 48%
“…This neuroprotective effect of IGF-I was predominantly mediated by activation of PI3-K and Akt. However, IGF-I has also been reported to increase the sensitivity of cerebellar granule cells to NMDAinduced excitotoxicity (49). In contrast to granule cells, we demonstrate here that preincubation with IGF-I provides modest neuroprotection from NMDA-induced neuronal apoptosis in cerebrocortical cultures.…”
Section: Discussionmentioning
confidence: 42%
“…Several lines of evidence have contributed to this co~ cept. Thus, IGF-1 induces the expression of functionally acl ve glutamate receptors in these neurons, and neutralizatio i of serum IGF-1 by a specific antibody reduces neuronal sul rival by 30-40% [29]. Although cerebellar granule neurons do not produce IGF-1 at any stage of development, they do ex I ,ress the IGF-1 receptor both in vivo [30] and in vitro (data no shown).…”
Section: Discussionmentioning
confidence: 99%